1997
DOI: 10.1124/mol.52.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Apoptosis in Metallothionein Null Cells

Abstract: Metallothioneins (MTs) are major intracellular, zinc-binding proteins with antioxidant properties. Mouse embryonic cells null for MT due to loss of functional MT I and II genes (MT-/-) were more susceptible to apoptotic death after exposure to tert-butyl hydroperoxide or the anti-cancer agents cytosine arabinoside, bleomycin, melphalan, and cis-dichlorodiammineplatinum(II) compared with wild-type mouse embryonic cells (MT+/+). We measured basal levels of the tumor suppressor protein p53 and the death effector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
82
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(91 citation statements)
references
References 35 publications
6
82
0
3
Order By: Relevance
“…The results showed that TBHP produced oxidative stress (Figure 1) and induced apoptotic cell death in the HepG2 cells (Figure 3). These results are consistent with previous other reports that in non-hepatocytes TBHP induced apoptosis through the induction of oxidative stress (Langley et al, 1993;Kondo et al, 1997).…”
Section: Tbhp (μM)supporting
confidence: 83%
“…The results showed that TBHP produced oxidative stress (Figure 1) and induced apoptotic cell death in the HepG2 cells (Figure 3). These results are consistent with previous other reports that in non-hepatocytes TBHP induced apoptosis through the induction of oxidative stress (Langley et al, 1993;Kondo et al, 1997).…”
Section: Tbhp (μM)supporting
confidence: 83%
“…MTs bind zinc and copper and presumably function in metal ion regulation and detoxification in peripheral tissues as well as in the CNS (4,33). Early studies suggested that MT-I ϩ II could have significant antioxidant capacity and functions (32,55,63), and recent reports with transgenic mice overexpressing these MT isoforms and with MT-I ϩ II KO mice fully support such roles (22,28,37,39,40,42,43). We have recently shown that the inflammatory response to glial cell death and the wound healing capacity of the CNS is severely impaired in MT-I ϩ II KO mice (49,50), suggesting a major role of these MT isoforms during CNS injury.…”
Section: Introductionmentioning
confidence: 76%
“…6 In addition, mouse embryonic cells null for MT due to loss of functional MT-1 and MT-2 genes were more susceptible to apoptotic death after exposure to cisplatin. 7 Nevertheless, results from 2 independent groups led to the conclusion that unexposed MT-1/2 knockout mice are viable and reproduce normally. 8,9 Although the role of MT in cisplatin susceptibility of normal kidney cells appears to be clear, the situation remains inconclusive for tumor cells.…”
mentioning
confidence: 99%
“…10 Furthermore, induction of MT synthesis by incubation of cell lines with dexamethasone also induced resistance against cisplatin. 7,11 MT content and MT mRNA levels correlated with level of resistance to cisplatin in several human small-cell lung-cancer cell lines. 12 Although a large number of studies have shown MT involvement in resistance to platinum compounds, its precise influence on susceptibility of tumor cells remains elusive since transfection of cell lines with MT-expression constructs also generated clones that are not more resistant 10,13 or that are even more susceptible.…”
mentioning
confidence: 99%